Anopheles (Kerteszia) cruzii (DIPTERA: CULICIDAE) IN PERIDOMICILIARY AREA DURING ASYMPTOMATIC MALARIA TRANSMISSION IN THE ATLANTIC FOREST: MOLECULAR IDENTIFICATION OF BLOOD-MEAL SOURCES INDICATES HUMANS AS PRIMARY INTERMEDIATE HOSTS - Kirchgatter, Karin; Tubaki, Rosa Maria; Malafronte, Rosely dos Santos; Alves, Isabel Cristina; Lima, Giselle Fernandes Maciel de Castro; Guimarães, Lilian de Oliveira; Zampaulo, Robson de Almeida; Wunderlich, Gerhard (Revista do Instituto de Medicina Tropical de São Paulo, 2014)
Anopheles (Kerteszia) cruzii has been implicated as the primary vector of human and simian malarias out of the Brazilian Amazon and specifically in the Atlantic Forest regions. The presence of asymptomatic human cases, parasite-positive wild monkeys and the similarity between the parasites infecting them support the discussion whether these infections can be considered as a zoonosis. Although many aspects of the biology of An. cruzii have already been addressed, studies conducted during outbreaks of malaria transmission, aiming at the analysis of blood feeding and infectivity, are missing in the Atlantic Forest. This study was conducted in the location of Palestina, Juquitiba, where annually the majority of autochthonous human cases are notified in the Atlantic Forest of the state of São Paulo. Peridomiciliary sites were selected for collection of mosquitoes in a perimeter of up to 100 m around the residences of human malaria cases. The mosquitoes were analyzed with the purpose of molecular identification of blood-meal sources and to examine the prevalence of Plasmodium. A total of 13,441 females of An. (Ker.) cruzii were collected. The minimum infection rate was calculated at 0.03% and 0.01%, respectively, for P. vivax and P. malariae and only human blood was detected in the blood-fed mosquitoes analyzed. This data reinforce the hypothesis that asymptomatic human carriers are the main source of anopheline infection in the peridomiciliary area, making the probability of zoonotic transmission less likely to happen.